Gas1 Regulates Patterning of the Murine and Human Dentitions through Sonic Hedgehog - Seppala, M.; Thivichon-Prince, B.; Xavier, G.M.; Shaffie, N.; Sangani, I.; Birjandi, A.A.; Rooney, J.; Lau, J.N.S.; Dhaliwal, R.; Rossi, O.; Riaz, M.A.; Stonehouse-Smith, D.; et al. (Journal of dental research, 2022)
The mammalian dentition is a serially homogeneous structure that exhibits wide numerical and morphological variation among multiple different species. Patterning of the dentition is achieved through complex reiterative molecular signaling interactions that occur throughout the process of odontogenesis. The secreted signaling molecule Sonic hedgehog (Shh) plays a key role in this process, and the Shh coreceptor growth arrest-specific 1 (Gas1) is expressed in odontogenic mesenchyme and epithelium during multiple stages of tooth development. We show that mice engineered with Gas1 loss-of-function mutation have variation in number, morphology, and size of teeth within their molar dentition. Specifically, supernumerary teeth with variable morphology are present mesial to the first molar with high penetrance, while molar teeth are characterized by the presence of both additional and absent cusps, combined with reduced dimensions and exacerbated by the presence of a supernumerary tooth. We demonstrate that the supernumerary tooth in Gas1 mutant mice arises through proliferation and survival of vestigial tooth germs and that Gas1 function in cranial neural crest cells is essential for the regulation of tooth number, acting to restrict Wnt and downstream FGF signaling in odontogenic epithelium through facilitation of Shh signal transduction. Moreover, regulation of tooth number is independent of the additional Hedgehog coreceptors Cdon and Boc, which are also expressed in multiple regions of the developing tooth germ. Interestingly, further reduction of Hedgehog pathway activity in Shhtm6Amc hypomorphic mice leads to fusion of the molar field and reduced prevalence of supernumerary teeth in a Gas1 mutant background. Finally, we demonstrate defective coronal morphology and reduced coronal dimensions in the molar dentition of human subjects identified with pathogenic mutations in GAS1 and SHH/GAS1, suggesting that regulation of Hedgehog signaling through GAS1 is also essential for normal patterning of the human dentition.